Synergistic interactions of nisin and Spirulina platensis extracts for foodborne pathogen control - Luana de Carvalho; Nathália Aparecida Andrade de Souza; Márcia Cristina Furlaneto; Luciana Furlaneto Maia; Eliane Colla (Acta Scientiarum. Biological Sciences, 2025)
The search for naturally derived antimicrobials has emerged due to an increasing concern about the use of synthetic ones. In this investigation, we examined the antibacterial mechanism and potential synergistic effect of Spirulina platensis extracts and Nisin in inhibiting the growth of 23 strains of Gram-positive and Gram-negative foodborne pathogens. We conducted four different extraction protocols to obtain S. platensis compounds, ultimately selecting the alcoholic acid-formic acid-sonication extraction due to its antimicrobial activity against 95.6% of the tested strains. Escherichia coli, Listeria monocytogenes, and Staphylococcus aureus were selected for further analysis. Tests for Minimum Inhibitory Concentration (MIC) and the Checkerboard test revealed MIC values ranging from 0.5 to 0.12 µg mL-1 for Nisin and from 0.5 to 0.06 µg mL-1 for the selected S. platensis extract. When combined, the MIC range was 0.12 to 0.078 µg mL-1. The combination of S. platensis extracts and Nisin showed synergistic effects (Fractional Inhibitory Concentration Index0.302 to 0.18). The growth of foodborne pathogens tested was inhibited after 2, 6, 12, and 24 h with the combination of the compounds. Flow cytometry analysis showed that bacterial membrane permeability of the L. monocytogenes strain increased, while Scanning Electron Microscopy (SEM) illustrated the leakage of intracellular material, indicating cell membrane disruption. These observations suggest that combining S. platensis and nisin could be a promising natural alternative to synthetic preservatives in the food industry.